Achieving greater efficiency and higher confidence in single‐cell cloning by combining cell printing and plate imaging technologies. (3rd October 2018) - Yim, Mandy; Shaw, David
Abstract : In recent years, health authorities have increased emphasis on demonstrating that a cell line, which is used for the generation of biologics, is clonally derived. Within the past few years, single‐cell manipulation technologies, especially microfluidic drop‐on‐demand dispensing, have gained increased attention in the biopharmaceutical industry. This work discusses the development and characterization of a single‐cell printing workflow followed by plate imaging. By combining single‐cell printing and plate imaging with manual image verification it is possible to, (1) dramatically reduce the number of microtiter plates needed during the single‐cell cloning of clinical cell lines, as compared with a limiting‐dilution single‐cell cloning workflow, and therefore reduce the number of high‐resolution images acquired and stored and (2) achieve >99.99% assurance that the cell lines derived from this workflow are clonally derived. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 34:1454–1459, 2018